The Effect of Prenatal Yoga on Perineal Lacerations in Maternity Mothers at Midwife's Independent Practice Place in the Working Area of Tanjunganom Public Health Center, Nganjuk Regency 2022 - Miftakhul Mu’alimah; Dewi Kartikasari; Sunaningsih; Yunita Puspita Sari Pakpahan (Journal of Global Research in Public Health, 2022)
Childbirth is a physiological process that allows a series of great changes in the mother to be able to give birth to her fetus through the birth canal. During the delivery process, the mother often has lacerations or tears in the perineum. According to a preliminary study conducted at BPM in the working area of puskemas Tanjunganom Nganjuk, it was found that out of 10 maternity mothers, 6 (60%) of them experienced 3rd degree lacerations and 2 (20%) had 2nd degree lacerations and 2 (20%) maternity mothers experienced 1st degree lacerations. The purpose of this study is to analyze the effect of pregnant yoga on the incidence of perineal lacerations in maternity mothers at midwife’s independent practice palace in the Working Area Of Tanjunganom’s Public Health, Nganjuk Regency 2022. The research method used is quasy experiment with desaign posttest only control design research. The sample in this study was maternity mothers in July until October 2022 who were distinguished between the control group and the treatment group. The results showed that there was an influence of pregnant yoga on the incidence of perineal lacerations in maternity mothers with a value of ρ value 0.000 < α 0.05 with a difference in lacerations of degrees 1 and 3. From the results of this study, it can be concluded that pregnant yoga is very effective in preparing the elasticity of the perineal muscles so that it can help to prevent rupture during the labor process.